Prognostic and clinicopathological significance of LOXL2 in cancers: A systematic review and meta‐analysis. Issue 11 (29th April 2019) - Zhang, Xuerui; Huang, Junfu; You, Fan; Li, Wang; Zou, Zhenhong
Abstract: Background: Lysyl oxidase‐like 2 (LOXL2) is an extracellular matrix (ECM)‐modifying enzyme which can regulate the tensile strength of connective tissues by crosslink of collagen and elastin. Numerous studies have claimed correlations between LOXL2 expression and prognosis or clinicopathological characteristics in various cancers. However, the validities of these claims are still in question. To address these experimental results, a meta‐analysis was done to assess the prognostic and clinicopathological significance of LOXL2 expression in various cancers. Methods: The keywords were used for searching systematically in PubMed, Web of Science, Embase, Wanfang database, and CNKI. Stata SE15.0 was used for meta‐analysis. The hazard ratio (HR) and odds ratios (ORs) were pooled to assess the relationship between LOXL2 expression and overall survival (OS), disease‐free survival (DFS), and clinicopathological parameters. Results: Seventeen studies with 3, 881 patients were considered as valid studies. The results indicated that the patients who had a positive LOXL2 expression had a shorter OS (HR 1.60, 95% CI 1.26–1.94, p  < 0.001) or DFS (HR 1.46, 95% CI 1.14–1.78, p  < 0.001). For clinicopathological parameters, statistical significances were presented in age (OR 1.34, 95% CI 1.13–1.58, p  = 0.001), lymph node metastasis (OR 2.20, 95% CI 1.37–3.53, p  < 0.001), tumor size (OR 1.46, 95% CI 1.15–1.85, p  = 0.002), and vascular invasion (OR 1.82, 95% CI 1.33–2.48, p  < 0.001). Conclusions: The results demonstrate that positive LOXL2 expression presents poorer OS and worse clinicopathological parameters. LOXL2 may be an effective biomarker to evaluate the prognosis in different type of cancers. Abstract : To address these experimental results, a meta‐analysis was done to assess the prognostic and clinicopathological significance of LOXL2 expression in various cancers. The results demonstrate that positive LOXL2 expression presents poorer OS and worse clinicopathological parameters. LOXL2 may be an effective biomarker to evaluate the prognosis in different type of cancers.